Profile of Young Acute Myocardial Infarction in Chittagong Medical College Hospital, Chittagong (Cardiovascular Journal, 2012)
Background: Coronary artery disease (CAD) is now an emerging epidemic in developing countries including Bangladesh. Younger people are being affected here more and more. Young individuals with acute myocardial infarction (AMI) may have unique presentation, risk factor, angiographic profile and outcome which may have an influence on the preventive strategies. This study is an attempt to investigate the same. Methods: Young patients (aged d” 40 yrs) with AMI admitted to the coronary care unit of Chittagong Medical College Hospital over a period of one year were included in the study. Assessments of the patients were done with clinical history, physical examination and systemic evaluation. Location and types (STEMI, NSTEMI) of myocardial infarction were determined by ECG and serum troponin- 1 assay. Blood for glucose and lipid profile was drawn within 24 hours of admission. High sensitivity testing for C-reactive protein (hs CRP) was done in all patients. Coronary angiography was done within 6 weeks of hospital discharge. Results: A total of 83 Patients with age d” 40 years were included .Age range were 21-40 years (34.21 ± 5.07 yrs). There were 71 male (85.5%). Male: female ratio was 5.9:1. Most of the young AMI patients presented lately to the hospital. Majority of these patients were thinly built, came from urban or semiurban areas, engaged in heavy physical activities and belonged to lower socioeconomic group. A positive family history of CAD was present in 18 patients (28.68 %). Smoking was the most prevalent risk factor followed by a raised serum triglyceride or low high density lipoprotein (HDL). A raised hs CRP was present in 47 patients (49.39%). The overall in hospital mortality was only 3.61 %. Coronary angiography done in 38 patients revealed single vessel disease in the majority. Conclusion: The study focuses our attention to the rising incidence of AMI in young individuals who are less prone to CAD. Early detection of AMI and timely intervention needs high index of suspicion in this age group. These young patients have got low BMI High TG, Low HDG High hs CRP & habit of smoking. Avoidance of smoking, controlling high TG and/or low HDL may reduce incidence of AMI among young patients. Use of high dose of statin at an early age in young persons with raised CRP may be considered. Keywords: Myocardial infarction; Young. DOI: http://dx.doi.org/10.3329/cardio.v4i1.9390 Cardiovasc. J. 2011; 4(1): 53-57